Die oor-en-weer beroep van predikante tussen die Nederduitse Gereformeerde Kerk en die Nederduitsch Hervormde Kerk van Afrika: 1862–1917 - Toit, Flip du (HTS teologiese studies, 2015)
The ongoing appointment of ministers between the Dutch Reformed Church and the Netherdutch Reformed Church of Africa: 1862–1917. This article highlights the situation prior to the establishment of the theological training of the Netherdutch Reformed Church of Africa (NDRCA). The training of ministers of the Dutch Reformed Church (DRC) started in 1859 with the establishment of the Theological Seminary at Stellenbosch. Since 1862 three churches operated in the then Transvaal (South African Republic). Many ministers of the DRC were called to serve in the NDRCA. The most notable were the Rev D.P. Ackerman and the Rev H.S. Bosman. They were called before the origin of the united church (of the NDRCA and the DRC) that existed between 1885 and 1892. After the split in 1892, they (as well as many others) continued as ministers in the DRC. The first lecturer of the NDRCA was called in 1917 − also a minister that was previously from the DRC. The calling of his successor sparked a major row. The NDRCA congregation of Pretoria called another minister from the DRC – the Rev H.D. van Broekhuizen. This eventually led to a special meeting of the General Assembly of the NDRCA in 1917 where his calling was eventually approved.